Penerapan Pendekatan Konstruktivisme Dalam Metode Cerita Dilema Moral - Aiman Faiz; Purwati (Jurnal Elementaria Edukasia, 2023)
This research aims to stimulate the ability to understand moral considerations for PGSD students as a provision for knowledge of character education theory. Understanding moral dilemmas is important in moral and character education strategies. The researcher used a qualitative approach with a descriptive method with data collection techniques using interviews through a zoom meeting platform with 71 students consisting of PGSD Muhammadiyah University Cirebon students and PGSD UNNES. The results of the study revealed that the application of the discussion of moral dilemmas to a constructive approach received a positive response from the students. The fact was found that discussions of moral dilemmas presented in learning through zoom meetings were able to stimulate critical thinking skills which increased the moral judgment abilities of PGSD students as prospective educators. This increase was found from the results of the discussion of students' moral dilemmas which showed maturity in thinking hypothetically. The discussion of moral dilemmas also provides an understanding from the perspective of others, so that listening to other people's reasons for making decisions can increase judgment. The importance of ability in moral judgment and reasoning is one of the processes that can guide individual moral decisions to be more mature.